Educational Systems and Practical Opportunities of Distance Education in Higher Education Institutions (Eurasian Journal of Engineering and Technology, 2022)
The article describes the content, functions, advantages and disadvantages of virtual education management systems in distance learning and its teaching in higher education institutions, their practical capabilities